Self-Care Practice and Associated Factors Among People Living with Type 2 Diabetes in Addis Ababa, Ethiopia: A Facility-Based Cross-Sectional Study - Wolderufael M (Dove Medical Press, 2021)
Meklit Wolderufael,1 Nebiyu Dereje2 1Department of Medicine, Myungsung Medical College, Addis Ababa, Ethiopia; 2Department of Public Health, Myungsung Medical College, Addis Ababa, EthiopiaCorrespondence: Nebiyu DerejeDepartment of Public Health, Myungsung Medical College, Addis Ababa 14972, EthiopiaTel +251978788638Email neba.jahovy@gmail.comIntroduction: Diabetes is a global public health threat with a considerably high burden in low- and middle-income countries. The application of self-care practice by people living with diabetes helps to manage diabetes and its complications, and to lengthen their life. However, the level of diabetes self-care practice in Ethiopia is very low.Methods: A cross-sectional study was conducted among people living with type 2 diabetes who were on follow-up from January 01 to 31, 2019 at Yekatit 12 Hospital. A systematic sampling technique was employed to recruit 354 study participants. A face-to-face interview was administered by trained data collectors using a structured questionnaire. Diabetes self-care practice was assessed by using Summary of Diabetes Self-Care Activities (SDSCA) scale. Multi-variable binary logistic regression analysis was carried out to identify factors associated with diabetes self-care practice.Results: More than half (52.0%, 95% CI: 49.9% - 57.1%) of the people living with diabetes had poor diabetes self-care practice. Poor self-care practice was associated with being unemployed and retired (AOR= 3.57, 95% CI 1.65– 7.72), having diabetes for ≥ 10 years (AOR= 1.78, 95% CI 1.07– 2.95), having comorbidity (AOR= 2.15, 95% CI 1.35– 3.43), not owning glucometer (AOR= 1.81, 95% CI 1.16– 2.83), not receiving diabetes education (AOR= 1.95, 95% CI 1.20– 3.18) and dissatisfaction with social support (AOR= 4.24, 95% CI 1.25– 14.40).Conclusion: Poor self-care practice was found to be substantial among people living with diabetes in Addis Ababa, with self-monitoring of blood glucose and regular exercise being the least performed. It is beneficial to focus more on lifestyle modifications and educating about the severity of the disease for better management of blood sugar levels and hindrance of complications.Keywords: type 2 diabetes, self-care practice, diabetes education, Ethiopia